Social support and physical activity in college and university students: a meta-analysis - Wang, Xiaolin; Yang, Xuezhen; Mohd Nasiruddin, Nasnoor Juzaily; Wei, Shasha; Dong, Delong; Samsudin, Shamsulariffin (SAGE Publications, 2024)
Although physical activity (PA) has a profound impact on health, many college and university students are still physically inactive. There is some evidence to suggest that social support (SS) could impact the PA levels of students, but the internal relationship and specific effects are not very clear. The purpose of this review was to determine the strength of the relationship between SS and PA and examine whether any potential associations differed in terms of age, gender, and region among college and university students. Studies were identified using the following electronic databases: PubMed, SPORTDiscus, Web of Science, and Sociological Abstracts. Moderator analyses investigating the effects of students’ age, gender, and region (nation) were performed. This review included 19 articles. The results showed total SS was significantly associated with PA (r = 0.30, 95% confidence interval [CI]: [0.22, 0.37], p < .001). With respect to different types of support, friend support was more strongly associated with PA than family support. Gender factors had a significant moderating effect on the correlation between SS and PA (QM = 17.433, p < .001). Separate analyses examining the moderating effects of gender (percentage of females) found that the association between SS and PA was stronger with the increase in female percentage. In conclusion, SS is an important factor associated with PA levels and should foster SS within intervention programs according to types of SS and gender differences to increase PA levels among college and university students.